Implementing the Love-Based Curriculum in Arabic Language Teaching: A Case Study at MTsN 1 Bukittinggi - Lissa Afrisandi; Fajriyani Arsya (Universitas Islam Negeri Imam bonjol Padang, 2026)
Arabic language learning in Indonesian madrasahs continues to face challenges, particularly in fostering students' learning motivation, meaningful engagement, and character development alongside linguistic competence. In response to these challenges, the Ministry of Religious Affairs of the Republic of Indonesia introduced the Love-Based Curriculum as a humanistic educational framework that integrates spiritual values, compassion, and character formation into the teaching and learning process. This study aims to analyze the implementation of the Love-Based Curriculum in Arabic language instruction at MTsN 1 Bukittinggi, covering the planning, implementation, and evaluation stages of instruction. This study employed a qualitative method with a descriptive approach. The participants consisted of one Arabic language teacher, one vice principal for curriculum affairs, and five seventh-grade students, while teaching modules, assessment instruments, and other instructional documents served as supporting data sources. Data were collected through classroom observations, semi-structured interviews, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing and verification. The findings reveal that the Love-Based Curriculum has been systematically implemented throughout all stages of Arabic language learning. At the planning stage, the values of love were integrated into teaching modules, learning objectives, instructional strategies, and assessment instruments. During the implementation stage, learning was conducted through joyful, meaningful, and mindful learning by integrating the five core values of love into classroom activities. A major finding of this study is that the curriculum transformed teachers' instructional orientation from emphasizing linguistic competence alone to fostering students' spiritual, emotional, and social development through Arabic language learning. Another significant finding is that the implementation of the curriculum strengthened humanistic teacher–student relationships, creating a psychologically supportive classroom environment that enhanced students' participation and confidence in learning Arabic. At the evaluation stage, teachers employed diagnostic, formative, and summative assessments that measured students' knowledge, skills, attitudes, and character development. The study concludes that the Love-Based Curriculum contributes to creating more humanistic, meaningful, and character-oriented Arabic language learning in madrasahs.